PEMBELAJARAN TATAP MUKA DI TENGAH PANDEMI COVID 19: Penelitian di Madrasah Tsanawiyah Al Huda Al Musri 1 Cianjur - Muhammad Makky; Supiana; Qiqi Yuliati Zaqiyah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The emergence of the Covid-19 pandemic has caused some educational institutions to stop carrying out teaching and learning activities online. However, Madrasah Tsanawiyah AL Huda AL Musri 1 Cianjur is one of the educational institutions that consistently carries out face-to-face teaching and learning activities throughout the era of the Covid-19 pandemic. This post intends to define the wisdom of implementing face-to-face teaching and learning activities in the midst of a Pandemic, the consequences of the wisdom of face-to-face teaching and learning activities in the midst of a pandemic, and supporting aspects and barriers to the wisdom of face-to-face teaching and learning activities in the midst of the Covid-19 pandemic at Madrasah Tsanawiyah Al Huda Al Musri 1 Cianjur. This paper is prepared using a problem research approach in a qualitative research method, the main information base is obtained from the Principal, teachers and students of Madrasah Tsanawiyah AL Huda AL Musri 1 and the inferior information base from the selection of Madrasah Tsanawiyah AL Huda AL Musri 1. The method of collecting information used is in the form of question and answer, monitoring and selection with 3 ways of information analysis, namely reducing information, presenting information and revoking conclusions. Face-to-face teaching and learning activities in the midst of the Covid-19 Pandemic at Madrasah Tsanawiyah AL Huda AL Musri 1 are carried out by reducing the length of teaching and learning activities as a result of the accumulation of activities outside the category, but people of age benefit because their children consistently welcome teaching and learning activities comfortably. The supporting aspect of the implementation of teaching and learning activities is the existence of a 24-hour mes system and the inhibiting aspect is the lack of tools and infrastructure.